Comparative Foliar Anatomy of Ten Species in the Genus Hibiscus Linn. in Nigeria - Adedeji, O.; Illoh, H. C. (2014)
The foliar anatomy of ten species of Hibiscus in Nigeria is described. The distinguishing characters of taxonomic value include the variation in the shapes of petioles in the proximal region, the variation in the number and arrangement of the vascular bundles, presence or absence of medullary bundles in the pith at the distal end of the petiole, types of trichomes on the lamina and petioles and presence or absence of cuticular striations on the epidermal surfaces. Druses of calcium oxalate crystals occur generally in the genus, however, occurrence, distribution and quantity of these crystals is quite diagnostic on the adaxial and abaxial epidermal surfaces of H. rostellatus.